Safety and efficacy of S-IROX (S-1, irinotecan and oxaliplatin combination therapy) in patients with advanced pancreatic cancer: A multicenter phase 1b dose-escalation and dose-expansion clinical trial. (October 2022) - Ohba, Akihiro; Ueno, Hideki; Shiba, Satoshi; Okano, Naohiro; Kobayashi, Takaaki; Nagashima, Fumio; Sasahira, Naoki; Sasaki, Mitsuhito; Imaoka, Hiroshi; Sakamoto, Yasunari; Kondo, Shunsuke; Morizane, Chigusa; et al.
Abstract: Background: This phase 1b trial evaluated the toxicity and efficacy of S-1, irinotecan, and oxaliplatin combination therapy (S-IROX) as first-line chemotherapy in patients with advanced pancreatic cancer (APC). Methods: Patients aged 20–75 years with APC and an Eastern Cooperative Oncology Group performance status of 0 or 1 were eligible to receive escalating doses of S-1 (60 or 80 mg m 2 ·day) on days 1–7, fixed doses of oxaliplatin (85 mg/m 2 ) biweekly, and escalating doses of irinotecan (150, 165, or 180 mg/m 2 ) once every 2 weeks. In the dose-escalation cohort, a 3 + 3 design was used to determine the maximum-tolerated dose (MTD) and explore the recommended dose (RD). A dose-expansion cohort was added to further evaluate the safety and efficacy of the combination. This trial was registered at UMIN-CTR (UMIN000012054). Results: Approximately 47 patients were enrolled, of whom 45 were eligible for the analysis. The MTD was not determined, but the RD was determined to be dose level 1 based on a review of data from each level. Among the 45 patients, the ORR was 51.1% [95% confidence interval (CI), 35.8–66.3%]. The median progression-free survival and median overall survival was 6.9 months (95% CI, 5.1–8.8 months) and 15.8 months (95% CI, 9.8–20.8 months), respectively. Common adverse events included neutropenia, elevated liver enzyme levels, diarrhoea, and nausea. Conclusions: The S-IROX regimen showed promising efficacy with manageable toxicities in Japanese patients with APC. A randomised phase 2/3 trial comparing S-IROX, mFOLFIRINOX, and gemcitabine plus nab-paclitaxel is currently ongoing (jRCTs031190009). Highlights: Phase 1b trial of S-1, irinotecan, and oxaliplatin in pancreatic cancer. The RD was S-1 80 mg/m 2, irinotecan 150 mg/m 2, and oxaliplatin 85 mg/m 2 . The ORR was 51.1%, and PFS and OS were better than those of the historical FOLFIRINOX.